Speakers' awareness and the use of do be vs. be after in Hiberno‐English. Issue 2 (June 2016) - Shimada, Tamami
ABSTRACT: This paper investigates the interface of social and linguistic factors in contact‐induced language change with data from Hiberno‐English (HE). The evidence from my survey suggests that morphosyntactic forms in HE are unevenly marked in speakers' subjective judgments of use, non‐use, Irishness and 'bad grammar'. This study particularly examines the cause of the contrasting judgements between the do be and be after forms. The examination leads to the suggestion of the constraint of morphosyntactic conformity and provides further theoretical perspectives on the role of speakers.